2004
DOI: 10.1007/s00018-003-3278-2
|View full text |Cite
|
Sign up to set email alerts
|

The never-ending story of peptide O -xylosyltransferase

Abstract: In a journey lasting 40 years from the first reports on its activity in the 1960s to its purification and the cloning of relevant complementary DNAs, peptide O-xylosyltransferase has finally arrived at the same point as many other enzymes. This enzyme, whose systematic name is UDP-alpha-D-xylose:proteoglycan core protein beta-D-xylosyltransferase (EC 2.4.2.26), catalyses the first step in the biosynthesis of chondroitin, dermatan and heparan sulphates in the endoplasmic reticulum and/or the cis-Golgi cisternae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 74 publications
1
59
0
Order By: Relevance
“…1A, indicated by double underlines). In addition, class I SLRP members typically contain a propeptide that may function as a recognition sequence for xylosyltransferase that catalyzes the initial step of the biosynthesis of CS or DS glycosaminoglycan chains (32). However, NPN contains neither this conserved propeptide region nor serine-glycine (SG) sequence required for the O-linked glycosaminoglycan attachment.…”
Section: Discussionmentioning
confidence: 99%
“…1A, indicated by double underlines). In addition, class I SLRP members typically contain a propeptide that may function as a recognition sequence for xylosyltransferase that catalyzes the initial step of the biosynthesis of CS or DS glycosaminoglycan chains (32). However, NPN contains neither this conserved propeptide region nor serine-glycine (SG) sequence required for the O-linked glycosaminoglycan attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Cycloheximide blocks the de novo synthesis of proteins, and the fungal metabolite BFA has been used to distinguish between proteins residing within the cis-/medial/ trans-cisternae and the trans-Golgi network. BFA causes the collapse of the contents of the cis-, medial, and trans-cisternae back to the ER, whereas proteins residing within the trans-Golgi network traffic to the microtubule organizing center (34,35). This redistribution allows the straightforward assignment of localization either in the Golgi cisterna or trans-Golgi network.…”
Section: Construction and Recombinant Expression Of Active Full-lengtmentioning
confidence: 99%
“…19,20 Many reports have indicated that modifications of the GAG tetrasaccharide core do exist and novel modified structures have been identified. [21][22][23][24] For example, sulfates have been found to be attached at two of the galactose sugar units via different linkages.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, in addition to sulfated galactose as described above, 25 sulfation typically occurs at N-acetyl glucosamine-glucuronic acid (GlcNAc-GlcA) disaccharide repeating units extended off of the GAG core. 19,20 Therefore, sulfated GlcA found in urinary αTM may be unique, as soluble human molecules recombinantly produced in CHO cells only generate immature, non-sulfated GAG tetrasaccharide and other shorter intermediates based on analysis of the released glycans from recombinant αTM. 30 This early report on the immature GAGs found in recombinant αTM is consistent with that for recombinant LCAT-Fc and other fusion molecules containing linker sequence with GSG sequence motif.…”
Section: Discussionmentioning
confidence: 99%